A Comprehensive Study on the Chemical, Biological, and Environmental Factors Shaping the Medicinal Value of Euphorbia hirta - J. B. Reshmi; P. S. Abitha; P. C. Divya; S. Grace Victoria; V. N. Meena Devi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Axial behavior of circular concrete composites confined with concrete canvas and GFRP - V. M. SharanKarthick; S. Divya; N. Shanmugasundaram; S. Praveen Kumar (Innovative Infrastructure Solutions, 2026)

Integrative network and structural analysis of Pinus derived phytosterols in diabetes associated pathways - P. Roshan Ali; Gutti Krishna Sri; Gojuvaka Sravanthi; Kavirayani Naga Lakshmi Shivani; Rajinikanth Sagapola; Kalasani Divya; V. V. Rajesham; Mitta Raghavendra; Dyvapu Lalitha Bhaskarini (In Silico Pharmacology, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Integrating TRIGRS and RAMMS for the spatiotemporal prediction of rainfall induced landslides and landslide trajectory: a case study - A. Musaib; V. Aparna; P. V. Divya (Natural Hazards, 2026)

Genetic diversity assessment of near-threatened endemic catfish Clarias dussumieri in Western Ghats, India: implications for conservation - Divya Prema Radhakrishnan; Divya Merin Jose; C. P. Abhilash; V. S. Basheer; Uttam Kumar Sarkar (Hydrobiologia, 2026)

Wild species Oryza rufipogon as a potential donor for development of interspecific backcross population in the background of Samba Mahsuri (BPT5204) and detection of yield enhancing QTLs - M. Sridhar; C. Gireesh; Divya Balakrishnan; M. Sujatha; M. S. Anantha; C. H. Raveendra; P. Senguttuvel; D. Srinivasa Chary; V. P. Bhadana; R. M. Sundaram (Plant Physiology Reports, 2025)

Unraveling allelic variations and population structure in wild species and cultivars of rice (Oryza spp.) for yield-related genes - Musku Sridhar; Divya Balakrishnan; M. S. Anantha; P. Senguttuvel; R. M. Sundaram; L. V. Subbarao; D. Aleena; Ch. Raveendra; S. Rathod; S. R. Chimmli; G. Padmavathi; M. Sujatha; et al. (Cereal Research Communications, 2025)

Comparison of clinical, radiological and outcome parameters in patients with progressive multifocal leukoencephalopathy (PML) with and without HIV infection: a cohort study - Farsana Mustafa; Anuj Ajayababu; Ajay Garg; Megha Brijwal; Divyani Garg; Manish Soneja; Aashish Choudhary; Lalit Dar; Shariq A. Shah; Venugopalan Y Vishnu; Animesh Ray; Neeraj Nischal; et al. (Journal of NeuroVirology, 2025)

Curcumin in feed lowers leptin and its receptor gene expression, alters fatty acid and amino acid profiles and improves the antioxidant activities in the muscle of tilapia, Oreochromis mossambicus - M. V. Sruthi; Divya Lekha (Aquaculture International, 2025)

Genetic Diversity and Population Structure Analysis in Avocado (Persea americana) Accessions of India - B. M. Muralidhara; T. Sakthivel; D. C. Lakshmana Reddy; G. Karunakaran; V. Venkatravanappa; Siddanna Savadi; Divya Vani Vaka; Ponnam Naresh; K. S. Shivashankara; R. Venugopalan; M. K. Honnabyraiah (Agricultural Research, 2025)

A review on advances in hybrid magnetic nanoparticles for microplastics removal: Mechanistic insights and emerging prospects - V. Divya; V.C. Deivayanai; K. Anbarasu; A. Saravanan; A.S. Vickram (Environmental Research, 2025)

Spatial prediction of soil carbon with deterministic and covariate-integrated geostatistical models - Nandaluru Kalpana; V. Divya Vijayan; Sahar Shaikh; S. Dharani (Environmental Monitoring and Assessment, 2025)

Efficient feature extraction using light-weight CNN attention-based deep learning architectures for ultrasound fetal plane classification - Arrun Sivasubramanian; Divya Sasidharan; V. Sowmya; Vinayakumar Ravi (Physical and Engineering Sciences in Medicine, 2025)

Deciphering mating type and population genetic landscape of Magnaporthe population adapted to millets and rice in blast hotspots of India - K. B. Palanna; Gutha Venkata Ramesh; Prasanna S. Koti; H. D. Vinaykumar; Divya Bhandhari; H. R. Raveendra; T. S. S. K. Patro; T. V. Krishna; T. E. Nagaraja; R. Madhusudhana; C. Tara Satyavathi (Archives of Microbiology, 2025)

The effect of α-tocopherol (vitamin E) on the phase behaviour of fully-hydrated dioleoyl phosphatidylcholine membranes - Chi Long Chan; Divya Malia; Miguel Paez-Perez; Laurent Sagalowicz; Olivier Schafer; Robert V. Law; Nicholas J. Brooks; John M. Seddon (Chemistry and Physics of Lipids, 2025)

Separating Historical Catches Among Pygmy Blue Whale Populations Using Recent Song Detections - Trevor A. Branch; Cole C. Monnahan; Emmanuelle C. Leroy; Fannie W. Shabangu; Ana Širović; Salvatore Cerchio; Suaad Al Harthi; Cherry Allison; Naysa Balcázar Cabrera; Dawn R. Barlow; Susannah V. Calderan; Michael C. Double; et al. (Marine Mammal Science, 2025)
In the Southern Hemisphere and northern Indian Ocean, there are at least five populations of pygmy blue whales, Balaenoptera musculus brevicauda , residing in the Northwest Indian Ocean (NWIO, Oman), central Indian Ocean (CIO, Sri Lanka), Southwest Indian Ocean (SWIO, Madagascar to Subantarctic), Southeast Indian Ocean (SEIO, Australia to Indonesia), and Southwest Pacific Ocean (SWPO, New Zealand). Each population produces a distinctive repeated song, but none have population assessments or reliable measures of historical whaling pressure. Here we created pygmy blue whale catch time series by removing Antarctic blue whale catches using length data and then fitting generalized additive models (based on latitude, longitude, and month) to contemporary song data (largely from 1995 to 2023) to allocate historical catches to the five populations. Most pygmy blue whale catches (97% of 12,207) were taken by Japanese and Soviet operations during 1959/1960 to 1971/1972, with the highest totals taken from the SWIO (6514), SEIO (2593), and CIO (2023), and lower catches from the NWIO (549) and SWPO (528). The resulting predicted annual catch assignments provide the first indication of the magnitude of whaling pressure on each population and are a key step toward assessing the status of these five pygmy blue whale populations.

Effect of integrated disease management modules against major diseases (bacterial blight/root rot and downy mildew) of opium poppy - Shivam Singh; R. S. Mishra; S. K. Singh; M. K. Maurya; J. R. Yadav; Divya Singh; Abhishek Kumar; V. V. Raghuvanshi (Vegetos, 2025)

Recent developments in the design of functional derivatives of edaravone and exploration of their antioxidant activities - R. Divya Mohan; Naveen V. Kulkarni (Molecular Diversity, 2025)

Wild introgression lines of Oryza nivara as potential donor for yield and seedling vigour traits and mapping associated genomic regions - D. Sai Teja; Divya Balakrishnan; P. Magudeeswari; Sonali Kar; P. Arun Kumar; G. Pranay; R. Pushpa; Kalyani M. Barbadikar; L. V. Subba Rao; N. Sarla; S. V. SaiPrasad; R. M. Sundaram (Euphytica, 2025)

From cognition to economic valuation of cultural ecosystem services – An evidence from Parambikulam tiger reserve, Kerala - Divya Soman; V. Anitha; Syam Viswanath; M. Sreeraj (Journal for Nature Conservation, 2025)

Significance of gender, brain region and EEG band complexity analysis for Parkinson’s disease classification using recurrence plots and machine learning algorithms - Divya Sasidharan; V. Sowmya; E. A. Gopalakrishnan (Physical and Engineering Sciences in Medicine, 2025)

Food Security Based Marine Life Ecosystem for Polar Region Conditioning: Remote Sensing Analysis with Machine Learning Model - Ganduri Srikanth; Divya Nimma; R. V. S. Lalitha; Pradeep Jangir; N. V. Siva Kumari; Arpita (Remote Sensing in Earth Systems Sciences, 2025)

Plant diversity and microbial interaction on soil carbon stock in the tropical homegardens: a nature-based solution to climate change - Athulya Tom; V. Divya Vijayan; T. K. Kunhamu; S. Sandeep; K. Surendra Gopal; V. Jamaludheen; B. R. Vishnu (Agroforestry Systems, 2025)

Geospatial assessment of agroforestry land use systems using very high-resolution satellite images and artificial intelligence - Shivam Trivedi; P. V. Vinod; B. Chandrasekaran; M. K. Nagashree; S. Rama Subramoniam; V. B. Manjula; Amrita Singh; J. K. Mani; Arun S. Suryavanshi; Sushilkumar B. Rehpade; Akash Goyal; N. R. Shankar Ram; et al. (Agroforestry Systems, 2024)

Identification and pathogenicity of mycoflora associated with leaf spot disease of Aloe vera - Divya Singh; V. P. Chaudhary; S. K. Singh; Shivam Singh; Jay Kumar Yadav; Harshita (Vegetos, 2024)

Multi-environment testing revealed the effect of yield genes on the grain yield stability in diverse rice germplasm - Aleena Dasari; Divya Balakrishnan; Santosha Rathod; P. V. R. Rao; Laksminarayana R. Vemireddy; C. N. Neeraja; S. Vanisri; K. N. Ranjith; R. M. Sundaram; Jyothi Badri (Cereal Research Communications, 2024)

Linkage mapping and quantitative trait loci detection for seedling vigor and grain size in advanced backcross introgression lines from wild accessions of Oryza nivara - P. Magudeeswari; Divya Balakrishnan; Yoshimichi Fukuta; Hiroki Saito; D. Saitheja; G. Pranay; R. Padmashree; Kalyani M Barbadikar; Jyothi Badri; P. Senguttuvel; K. Sruthi; D. Ladhalakshmi; et al. (Genetic Resources and Crop Evolution, 2024)

Morphological and molecular data establishes Clinostomum dolichorchum n. sp. (Digenea: Clinostomidae) in the great blue heron Ardea herodias L. and American bullfrog Rana catesbeiana Shaw - Jonah A. Nguyen; Ethan T. Woodyard; Chris T. McAllister; Susan V. Marcquenski; Divya Rose; Celene M. Slifka; Logan R. S. Robison; Matt J. Griffin; T. Graham Rosser (Systematic Parasitology, 2024)

Antimicrobial resistance landscape in a metropolitan city context using open drain wastewater-based metagenomic analysis - Manas Kumar Madhukar; Nirupama Singh; V Rajesh Iyer; Divya Tej Sowpati; Karthik Bharadwaj Tallapaka; Rakesh Kumar Mishra; Shivranjani Chandrashekhar Moharir (Environmental Research, 2024)

Stability analysis and genetic mapping for yield traits of rice wild introgression lines - N. P. S. De Silva; P. Magudeeswari; Divya Balakrishnan; V. Gouri Shankar; B. Kavitha; A. Krishnamraju; P. Prashanthi; K. Vaibhav; D. S. Chary; S. N. C. V. L. Pushpavalli; Sarla Neelamraju (Cereal Research Communications, 2024)

SIRT6 in Regulation of Mitochondrial Damage and Associated Cardiac Dysfunctions: A Possible Therapeutic Target for CVDs - K. P. Divya; Navjot Kanwar; P. V. Anuranjana; Gautam Kumar; Fathima Beegum; Krupa Thankam George; Nitesh Kumar; K. Nandakumar; Abhinav Kanwal (Cardiovascular Toxicology, 2024)

Synthesis, Structural, and Optical Properties of 2-(2-methyl 8-hydroxyquinoline) Magnesium Nanorods for Optical Display Systems - J. P. Suchitra; J. Christina Rhoda; V. Bharathi Devi; P. Divya; Helen Merina Albert (Journal of Fluorescence, 2024)

Biometeorological analysis on the molecular incidence of babesiosis and ehrlichiosis in dogs - Y. Ajith; Sasi Adithya; Varuna P. Panicker; N. Athira; V. Beena; M. Saifudeen Safeer; P. Preena; A. R. Nisha; C. Divya; S. G. Sangeetha; C. G. Umesh; R. C. Sundararajan; et al. (Theoretical and Applied Climatology, 2024)

Flowering onset time is regulated by microRNA-mediated trehalose-6-phosphate signaling in Cajanus cajan L. under elevated CO2 - Divya K. Unnikrishnan; Rachapudi V. Sreeharsha; Shalini Mudalkar; Attipalli R. Reddy (Physiology and Molecular Biology of Plants, 2024)

Low clouds over the subtropical Indian Ocean and sub-seasonal circulation associations with the Indian summer monsoon - T. Gokul; R. K. Vellore; D. C. Ayantika; V. Divya; R. Krishnan; M. J. K. Reji (Climate Dynamics, 2024)

Resolving taxonomic ambiguity and distribution of Tremoctopus gracilis (Cephalopoda: Tremoctopodidae) based on molecular evidence - Kurichithara K. Sajikumar; Geetha Sasikumar; Divya Viswambharan; Summaya Rahuman; N. S. Jeena; Nedumpally Vineesh; C. P. Binesh; K. P. Said Koya; V. Mahesh; Prathibha Rohit; P. K. Asokan; Smruthu Mohan; et al. (Marine Biology, 2024)

Diversity of Indian rice cultivars and landraces for seedling vigour and their association for yield related traits - Sai Teja Dayala; Divya Balakrishnan; Sonali Kar; J. L. Ganguli; L. V. Subba Rao; R. M. Sundaram (Vegetos, 2024)

Identification of nitric oxide mediated defense signaling and its microRNA mediated regulation during Phytophthora capsici infection in black pepper - Srinivasan Asha; Divya Kattupalli; Mallika Vijayanathan; E. V. Soniya (Physiology and Molecular Biology of Plants, 2024)

Identification and validation of blast resistance Pi1 gene in the derived mapping population of rice variety, NLR34449 through molecular markers - Dasari Aleena; V. Padma; G. Rekha; M. S. Prasad; M. S. Madhav; E. Punniakoti; T. Dilip; P. Sinha; M. Kousik; M. A. Das; M. Anila; Lal Ahmmed; et al. (Indian Phytopathology, 2023)

Monsoon paddy crop discrimination using machine learning algorithms to multi-temporal Sentinel-1A (C-band) data in Alathur block of Palakkad district of Kerala state, India - Divya Vijayan V; Dnyaneshwar Arjun Madane; Dipanwita Haldar (Paddy and Water Environment, 2023)

Taxonomic study of Eteoryctis syngramma (Meyrick, 1914) (Lepidoptera: Gracillariidae) immature and adult - R. Divya; N. Chitra; V. Balasubramani; R. Arulprakash; A. Sankari (International Journal of Tropical Insect Science, 2023)

N-Glycoprofiling of immunoglobulin G and lactoperoxidase from sheep milk using LC-MS/MS - M. Sudarshan; V. Divya Shree; P. Jyothibai; B.S. Gnanesh Kumar (International Dairy Journal, 2023)

Novel Biocompatible Green Silver Nanoparticles Efficiently Eliminates Multidrug Resistant Nosocomial Pathogens and Mycobacterium Species - Shahbaz Aman; Narinder Kaur; Divya Mittal; Deepanjali Sharma; Komal Shukla; Bharat Singh; Anchita Sharma; Samarjeet Singh Siwal; Vijay Kumar Thakur; Hemant Joshi; Raju Gupta; Reena V. Saini; et al. (Indian Journal of Microbiology, 2023)

Synthesis and biological evaluation of 1,2,3-triazole hybrids of 4-methoxy ethyl cinnamate isolated from Hedychium spicatum (Sm) rhizomes: identification of antiproliferative lead actives against prostate cancer - G. Swarna Kumari; Bandi Siva; S. Divya Reddy; V. Lakshma Nayak; Ashok K. Tiwari; Bhattu Ganga Rao; K. Suresh Babu (Natural Product Research, 2023)

Genetic diversity analysis and population structure in a rice germplasm collection of different maturity groups - Swapna Jadhav; Divya Balakrishnan; V Gouri Shankar; Kavitha Beerelli; Gowthami Chandu; Sarla Neelamraju (Journal of Plant Biochemistry and Biotechnology, 2022)

Interference of bio-control Trichoderma to enhance physical and physiological strength of sugarcane during Pokkah boeng infection - Raghvendra Tiwari; Kajal Chandra; S. K. Shukla; V. P. Jaiswal; Natarajan Amaresan; Abhay Kumar Srivastava; Asha Gaur; Divya Sahni; Rajesh Kumar Tiwari (World Journal of Microbiology and Biotechnology, 2022)

Correction to: Quantitative proteomic analysis reveals differential modulation of crucial stage specific proteins during promastigote to amastigote differentiation in Leishmania donovani - Chinmayee Bar Routaray; Vaibhavee Choudhari; Divya Prakash; Rajendra Patil; Surabhi Jagtap; Shakuntala Bai; Mahesh J. Kulkarni; Suresh V. Kuchipudi; Kalpana Pai (Journal of Proteins and Proteomics, 2022)

Yield Estimation of Cassava Using SIMCAS Model Over the Major Cassava Growing Regions in India - Divya K. Lekshmanan; Raji Pushpalatha; V. S. Santhosh Mithra; S. Sunitha; James George; M. Velmurugan; P. Ashok; N. V. Mhasker; K. D. Desai; R. Shiny; Gangadharan Byju (Agricultural Research, 2022)

Genetic stock identification in Perna viridis (Linnaeus1758) from the Indian Peninsula by using microsatellite markers - P. R. Divya; Linu Joy; Sunitha Poulose; P. M. Elizabeth Jency; V. S. Basheer; A. Kathirvelpandian; Vindhya Mohindra; Kuldeep Kumar Lal (Molecular Biology Reports, 2022)

Gender differences in progressive supranuclear palsy - Rohan R. Mahale; Syam Krishnan; K. P. Divya; V. T. Jisha; Asha Kishore (Acta Neurologica Belgica, 2022)

Quantitative proteomic analysis reveals differential modulation of crucial stage specific proteins during promastigote to amastigote differentiation in Leishmania donovani - Chinmayee Bar Routaray; Vaibhavee Choudhari; Divya Prakash; Rajendra Patil; Surabhi Jagtap; Shakuntala Bai; Mahesh J. Kulkarni; Suresh V. Kuchipudi; Kalpana Pai (Journal of Proteins and Proteomics, 2022)

Benzofuran pyran hybrid prevents glucocorticoid induced osteoporosis in mice via modulation of canonical Wnt/β-catenin signaling - Ashish Kumar Tripathi; Divya Rai; Priyanka Kothari; Pragati Kushwaha; Koneni V. Sashidhara; Ritu Trivedi (Apoptosis, 2022)

A comprehensive study on preparedness, impacts, response and recovery from tropical severe cyclonic storm ‘GAJA’: lessons for the future - S. Leo George; K. Balasubramani; Sulochana Shekhar; E. Venkatesham; K. Arun Prasad; Aakriti Grover; Dinabandhu Mahata; Ashish Kumar; V. V. Ashique; R. S. Libina; Divya Rajeswari Swaminathan; A. Balasundareshwaran; et al. (Journal of Coastal Conservation, 2021)

Re-Description of Sillago malabarica, Silver Whiting from Southern Indian Waters - P. R. Divya; Rahul G. Kumar; Linu Joy; C. P. Rajool Shanis; V. S. Basheer; K. K. Lal (Thalassas: An International Journal of Marine Sciences, 2021)

C3G Regulates STAT3, ERK, Adhesion Signaling, and Is Essential for Differentiation of Embryonic Stem Cells - Vijay V. Vishnu; Bh. Muralikrishna; Archana Verma; Sanjeev Chavan Nayak; Divya Tej Sowpati; Vegesna Radha; P. Chandra Shekar (Stem Cell Reviews and Reports, 2021)
Summary C3G (RAPGEF1), engaged in multiple signaling pathways, is essential for the early development of the mouse. In this study, we have examined its role in mouse embryonic stem cell self-renewal and differentiation. C3G null cells generated by CRISPR mediated knock-in of a targeting vector exhibited enhanced clonogenicity and long-term self-renewal. They did not differentiate in response to LIF withdrawal when compared to the wild type ES cells and were defective for lineage commitment upon teratoma formation in vivo. Gene expression analysis of C3G KO cells showed misregulated expression of a large number of genes compared with WT cells. They express higher levels of self-renewal factors like KLF4 and ESRRB and show high STAT3 activity, and very low ERK activity compared to WT cells. Reintroduction of C3G expression in a KO line partially reverted expression of ESRRB, and KLF4, and ERK activity similar to that seen in WT cells. The expression of self-renewal factors was persistent for a longer time, and induction of lineage-specific markers was not seen when C3G KO cells were induced to form embryoid bodies. C3G KO cells showed poor adhesion and significantly reduced levels of pFAK, pPaxillin, and Integrin-β1, in addition to downregulation of the cluster of genes involved in cell adhesion, compared to WT cells. Our results show that C3G is essential for the regulation of STAT3, ERK, and adhesion signaling, to maintain pluripotency of mouse embryonic stem cells and enable their lineage commitment for differentiation. Graphical abstract

Synthesis and Characterization of a Novel Heterocyclic Schiff Base and Development of a Fluorescent Sensor for Vitamin B12 - Savitha Devaswamparambil Pradeep; Deepa Sebastian; Anjali Krishna Gopalakrishnan; Divya Kizhakkeppurath Manoharan; Dhanya Thaikatt Madhusudhanan; Puzhavoorparambil V. Mohanan (Journal of Fluorescence, 2021)

Growth, seed yield and nutritional characteristics of pigeonpea grown under elevated CO2 atmosphere - Divya K. Unnikrishnan; Rachapudi V. Sreeharsha; Attipalli R. Reddy (Acta Physiologiae Plantarum, 2021)

Effect of PDGF-B Gene-Activated Acellular Matrix and Mesenchymal Stem Cell Transplantation on Full Thickness Skin Burn Wound in Rat Model - Tamilmahan Paramasivam; Swapan Kumar Maiti; Sangeetha Palakkara; Rashmi; Divya Mohan; H. V. Manjunthaachar; K. Karthik; Naveen Kumar (Tissue Engineering and Regenerative Medicine, 2021)

A comparison of zooplankton assemblages in Nansi Lake and Hongze Lake, potential influences of the East Route of the South-to-North Water Transfer Project, China - Kandathil Radhakrishnan Divya; Shasha Zhao; Yushun Chen; Fei Cheng; Lei Zhang; Jiao Qin; Thundiparambil Sathrajith Arunjith; V. Bjorn Schmidt; Songguang Xie (Journal of Oceanology and Limnology, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Control over MoSe2 formation with vacuum-assisted selenization of one-step electrodeposited Cu-In-Ga-Se precursor layers - Sreekanth Mandati; Prashant Misra; Divya Boosagulla; Narasinga Rao Tata; Sarada V. Bulusu (Environmental Science and Pollution Research, 2021)

Identification of potential Mpro inhibitors for the treatment of COVID-19 by using systematic virtual screening approach - Ashish M. Kanhed; Dushyant V. Patel; Divya M. Teli; Nirav R. Patel; Mahesh T. Chhabria; Mange Ram Yadav (Molecular Diversity, 2021)

Inheritance of leaf rust resistance in four popular Indian durum wheat cultivars - A. Divya; T. L. Prakasha; A. N. Mishra; S. Chand; K. S. Solanki; Pramod Prasad; S. V. Sai Prasad (Indian Phytopathology, 2020)

Assessment of genetic diversity and development of core germplasm in durum wheat using agronomic and grain quality traits - Divya Ambati; Rahul M. Phuke; V. Vani; S. V. Sai Prasad; Jang Bahadur Singh; Chandra Prakash Patidar; Prakash Malviya; Amit Gautam; Vijay G. Dubey (Cereal Research Communications, 2020)

Population connectivity and genetic structure of Asian green mussel, Perna viridis along Indian waters assessed using mitochondrial markers - P. R. Divya; P. M. Elizabeth Jency; Linu Joy; A. Kathirvelpandian; Rajeev Kumar Singh; V. S. Basheer (Molecular Biology Reports, 2020)

Genotype by Environment (G×E) Interaction Study on Yield Traits in Different Maturity Groups of Rice - Swapna Jadhav; Divya Balakrishnan; Gouri Shankar V; Kavitha Beerelli; Gowthami Chandu; Sarla Neelamraju (Journal of Crop Science and Biotechnology, 2019)

Genetics of novel brown planthopper Nilaparvata lugens (Stål) resistance genes in derived introgression lines from the interspecific cross O. sativa var. Swarna × O. nivara - S. Akanksha; V. Jhansi Lakshmi; Arun Kumar Singh; Yamini Deepthi; P. M. Chirutkar; Ramdeen; Divya Balakrishnan; N. Sarla; S. K. Mangrauthia; T. Ram (Journal of Genetics, 2019)

Bioimaging Applications of Carbon dots (C. dots) and its Cystamine Functionalization for the Sensitive Detection of Cr(VI) in Aqueous Samples - Roshni V.; Varsha Gujar; Heena Pathan; Sehbanul Islam; Madhumita Tawre; Karishma Pardesi; Manas Kumar Santra; Divya Ottoor (Journal of Fluorescence, 2019)

Deciphering demographic history and fine-scale population structure of cobia, Rachycentron canadum (Pisces: Rachycentridae) using microsatellite and mitochondrial markers - P. R. Divya; Joy Linu; C. Mohitha; A. Kathirvelpandian; P. Manoj; V. S. Basheer; A. Gopalakrishnan (Marine Biodiversity, 2019)

Caste-Specific Expression of Na+/K+-ATPase in the Asian Weaver Ant, Oecophylla smaragdina (Fabricius, 1775) - C C Sheeja; V V Thushara; L Divya (Neotropical Entomology, 2018)

Identification and feld evaluation of female sex pheromone of leaf-eating caterpillar, Opisina arenosella (Lepidoptera: Oecophoridae) - K. R. M. Bhanu; D. R. Hall; R. V. Awalekar; M. Chandrashekharaiah; T. N. Divya; M. S. Prabhakara; K. P. Jayanth (International Journal of Tropical Insect Science, 2018)

Overfishing and Climate Drives Changes in Biology and Recruitment of the Indian Oil Sardine Sardinella longiceps in Southeastern Arabian Sea - Vasant Kripa; Kolliyil S. Mohamed; K. P. Said Koya; R. Jeyabaskaran; D. Prema; Shelton Padua; Somy Kuriakose; P. S. Anilkumar; Preetha G. Nair; T. V. Ambrose; A. M. Dhanya; K. S. Abhilash; et al. (Frontiers in Marine Science, 2018)

Dimethylarginine dimethylaminohydrolase-1 (DDAH1) is frequently upregulated in prostate cancer, and its overexpression conveys tumor growth and angiogenesis by metabolizing asymmetric dimethylarginine (ADMA) - Karthik Reddy Kami Reddy; Chandrashekhar Dasari; Divya Duscharla; Bhukya Supriya; N. Sai Ram; M. V. Surekha; Jerald Mahesh Kumar; Ramesh Ummanni (Angiogenesis, 2018)

Synthesis, antioxidant, and antiviral properties of pyrimidinylsulfamoyl azolyl acetamides - Kuppi Reddy Gari Divya; Donthamsetty V. Sowmya; Suram Durgamma; Vadlamudi Tharanath; Divi Venkataramana Sai Gopal; Malaka Venkateshwarulu Jyothi Kumar; Chippada Appa Rao; Adivireddy Padmaja; Venkatapuram Padmavathi (Medicinal Chemistry Research, 2017)

Modulation of digestive enzymes, GH, IGF-1 and IGF-2 genes in the teleost, Tilapia (Oreochromis mossambicus) by dietary curcumin - Sebastian J. Midhun; Damodaran Arun; Lincy Edatt; M. V. Sruthi; V. V. Thushara; Oommen V. Oommen; V. B. Sameer Kumar; Lekha Divya (Aquaculture International, 2016)

PPIA rs6850: A > G single-nucleotide polymorphism is associated with raised plasma cyclophilin A levels in patients with coronary artery disease - A. Vinitha; V. Raman Kutty; A. Vivekanand; G. Reshmi; G. Divya; S. Sumi; K. R. Santosh; N. S. Pratapachandran; Mullassari S. Ajit; C. C. Kartha; Surya Ramachandran (Molecular and Cellular Biochemistry, 2016)

Characterization of microsatellite markers in silver pomfret, Pampus argenteus (Perciformes: Stromateidae) through cross-species amplification and population genetic applications - C. MOHITHA; LINU JOY; P. R. DIVYA; A. GOPALAKRISHNAN; V. S. BASHEER; MOHAMMED KOYA; J. K. JENA (Journal of Genetics, 2015)

Canopy Temperature as a Selection Parameter for Grain Yield and Its Components in Durum Wheat Under Terminal Heat Stress in Late Sown Conditions - Amit Gautam; S. V. Sai Prasad; Anjana Jajoo; Divya Ambati (Agricultural Research, 2015)

Physiological and Molecular Insights to Drought Responsiveness in Erianthus spp. - Sruthy Maria Augustine; Divya P. Syamaladevi; M. N. Premachandran; V. Ravichandran; N. Subramonian (Sugar Tech, 2015)

Molecular phylogenetics of three species of the genus Rastrelliger using mitochondrial DNA markers - V. S. Basheer; C. Mohitha; N. Vineesh; P. R. Divya; A. Gopalakrishnan; J. K. Jena (Molecular Biology Reports, 2015)

Overexpression of EaDREB2 and pyramiding of EaDREB2 with the pea DNA helicase gene (PDH45) enhance drought and salinity tolerance in sugarcane (Saccharum spp. hybrid) - Sruthy Maria Augustine; J. Ashwin Narayan; Divya P. Syamaladevi; C. Appunu; M. Chakravarthi; V. Ravichandran; Narendra Tuteja; N. Subramonian (Plant Cell Reports, 2015)

A quick method to screen high and low yielding wheat cultivars exposed to high temperature - Amit Gautam; Divya Agrawal; S. V. SaiPrasad; Anjana Jajoo (Physiology and Molecular Biology of Plants, 2014)

Urgency for sustainable development in coastal urban areas with reference to weather pattern, land use, and water quality - A. M. Sheela; J. Letha; K. Swarnalatha; K. V. Baiju; Divya Sankar (Environmental Monitoring and Assessment, 2014)

Flavonoid as chemotaxonomic markers in endemic/endangered species of Rauvolfia from Southern Western Ghats of India: A preliminary study - V. Divya Nair; R. Panneerselvam; R. Gopi (Plant Biosystems, 2013)

Experimental study of the interspecific competition between two sibling marine herbivorous rotifers in relation to food availability and initial population density - S. P. Divya; K. Kathiresan; P. Asha; V. Sekar; R. Rajasekaran (Acta Oceanologica Sinica, 2012)

Effect of triadimefon: a triazole fungicide on oxidative stress defense system and eugenol content in Ocimum tenuiflorum L. - V. Divya Nair; R. Gopi; M. Mohankumar; J. Kavina; R. Panneerselvam (Acta Physiologiae Plantarum, 2012)

Cloning and characterization of truncated cry1Ab gene from a new indigenous isolate of Bacillus thuringiensis - Sandhya Darsi; G. Divya Prakash; V. Udayasuriyan (Biotechnology Letters, 2010)

16SrRNA and enzymatic diversity of culturable bacteria from the sediments of oxygen minimum zone in the Arabian Sea - Baby Divya; K. V. Soumya; Shanta Nair (Antonie van Leeuwenhoek, 2010)